Care of the soul : a guide for cultivating depth and sacredness in everyday life - Moore, Thomas, 1940- (New York, NY : HarperCollins, 1992)
A guide that shows how to add spirituality, depth, and meaning to modern day life by nurturing the soul.
I. Care of the soul --
1. Honoring symptoms as a voice of the soul --
II. Care of the soul in everyday life --
2. The myth of family and childhood --
3. Self-love and its myth : narcissus and narcissism --
4. Love's initiations --
5. Jealousy and envy : healing poisons --
6. The soul and power --
7. Gifts of depression --
8. The body's poetics of illness --
9. The economics of soul : work, money, failure, and creativity --
III. Spiritual practice and psychological depth --
10. The need for myth, ritual, and a spiritual life --
11. Wedding spirituality and soul --
IV. Care of the world's soul --
12. Beauty and the reanimation of things --
13. The sacred arts of life.
Includes bibliographical references (p. [311]-312.
Keywords: Spiritual life; Psychology, Religious